Art and Craft in local economic development: Tourism possibilities in Mtubatuba Local Municipality - Jabulani Nyawo; Betty C Mubangizi (African Journal of Hospitality, Tourism and Leisure, 2015)

(untitled)
Since 1994, the support for small, medium and micro-enterprises (SMMEs) in South Africa has been a common theme in central government policy and planning. However, numerous enterprises in the rural areas have not fully benefited from such state policies. This paper reports on a study that critically examined the role of local government in the development of the art and craft sector as a Local Economic Development (LED) initiative. The study employed a qualitative study design and drew on interviews, on-site visits and participant observations so as to gain perceptions and understanding of the art and craft sector. Secondary data in the form of publications, government reports and policy positions were also used during the analysis and interpretation of the data. The results of the study show that the art and craft sector is vital for rural communities as it addresses some of the socio-economic challenges that communities face and invaluably contributes to tourism. Results further suggest that without the assistance of other LED stakeholders, especially local government, growth and development of this sector will remain a challenge.